2016
DOI: 10.18632/oncotarget.7283
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase A (MAO A) inhibitors decrease glioma progression

Abstract: Glioblastoma (GBM) is an aggressive brain tumor which is currently treated with temozolomide (TMZ). Tumors usually become resistant to TMZ and recur; no effective therapy is then available. Monoamine Oxidase A (MAO A) oxidizes monoamine neurotransmitters resulting in reactive oxygen species which cause cancer. This study shows that MAO A expression is increased in human glioma tissues and cell lines. MAO A inhibitors, clorgyline or the near-infrared-dye MHI-148 conjugated to clorgyline (NMI), were cytotoxic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 21 publications
2
88
0
1
Order By: Relevance
“…It finally leads to mitochondrial biogenesis, metabolic reprogramming, and tumor cell differentiation [104]. 3Сlorgyline alone or with TMZ acts as monoamine oxidase A inhibitor and reduces tumor growth [125]. (4) TCA clomipramine and SSRIs directly interact with complex III of respiratory chain, decreasing O2 consumption and stimulating reactive oxygen species generation.…”
Section: Mitochondria Are the Central Hub Of The "Intrinsic" Apoptotimentioning
confidence: 99%
“…It finally leads to mitochondrial biogenesis, metabolic reprogramming, and tumor cell differentiation [104]. 3Сlorgyline alone or with TMZ acts as monoamine oxidase A inhibitor and reduces tumor growth [125]. (4) TCA clomipramine and SSRIs directly interact with complex III of respiratory chain, decreasing O2 consumption and stimulating reactive oxygen species generation.…”
Section: Mitochondria Are the Central Hub Of The "Intrinsic" Apoptotimentioning
confidence: 99%
“…In most cell types in the body, an enzyme was discovered by Mary Bernheim in the liver and was called the name of the tyramine oxide [16]. MAO plays a crucial role in some mental and neurological disorders, including depression disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of MAOA has also been found in cholangiocarcinoma, Hodgkin's lymphoma and glioma. [12][13][14] A recent research result indicated that nonsmall cell lung cancer (NSCLC) tissues exhibited upregulation of MAOA compared with surrounding normal lung tissues. 15 Furthermore, a close relationship has been observed between increased MAOA expression in NSCLC tissues and Slug, N-cadherin and TWIST expression, EMT and the development of clinicopathological features of NSCLC such as later stage and lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%